2007
DOI: 10.1103/physrevb.75.201402
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure analysis of atomically smoothBaBiO3Films

Abstract: (MSRI) we analyze the surface structure of an atomically smooth BaBiO3 film grown by molecular beam epitaxy. We demonstrate high sensitivity of the TOF-SARS and MSRI spectra to slight changes in the orientation of the ion scattering plane with respect to the crystallographic axes. The observed angle dependence allows us to clearly identify the termination layer as BiO2. Our data also indicate that angle-resolved MSRI data can be used for high resolution studies of surface structure of complex oxide thin films. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 18 publications
2
30
1
Order By: Relevance
“…Deposition at a higher temperature ͑873 K͒ gave a film with Bi 2 O 3 impurities. Recently, Gozar et al 8 analyzed the surface structure of atomically smooth BaBiO 3 films using sophisticated methods such as low-energy timeof-flight scattering and recoil spectroscopy and mass spectroscopy of recoiled ions, and they found that the in-plane cell parameter was very close to that of the simple perovskite structure. Our results are similar to their findings in the sense that the BBO film adopted a cubic structure different from the distorted structures reported for the bulk-BBO phase.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Deposition at a higher temperature ͑873 K͒ gave a film with Bi 2 O 3 impurities. Recently, Gozar et al 8 analyzed the surface structure of atomically smooth BaBiO 3 films using sophisticated methods such as low-energy timeof-flight scattering and recoil spectroscopy and mass spectroscopy of recoiled ions, and they found that the in-plane cell parameter was very close to that of the simple perovskite structure. Our results are similar to their findings in the sense that the BBO film adopted a cubic structure different from the distorted structures reported for the bulk-BBO phase.…”
mentioning
confidence: 96%
“…Many experimental and theoretical studies have been conducted to elucidate the nature of the BBO and BKBO phases. [2][3][4][5][6][7][8][9][10][11][12][13][14] Below 750-800 K, BBO has both breathing and tilting distortions and is rhombohedral ͑R3͒ or monoclinic ͑I2 / m͒. Above 750-800 K, the crystal is cubic with only the breathing distortion ͑space group: Fm3m͒.…”
mentioning
confidence: 97%
“…Increase of the surface roughness broadens the structure in the recoiled features. 25 However, the angular resolution of our setup is not sufficient to measure this broadening. Despite the suitability of AR-MSRI to determine the dominant termination layer, the ability to prove perfect single termination can be compromised by surface roughness.…”
Section: B Ar-msrimentioning
confidence: 95%
“…An interesting area in nanoengineering of materials was opened in a series of experiments by Bozovič et al [1] on atomically perfect stacks of selectively doped perovskite layers. These and some other papers [2,3] mainly used periodic multilayered structures where essential new electronic effects, as interface SC between nominally non-SC layers [3], appeared due to charge redistribution between layers and related shifts of in-plane energy bands. The basic condition for SC to appear within few perovskite layers or even in a single layer is that the local density of hole charge carriers occurs within a definite, rather narrow, interval: p min ≥ p ≥ p max with p min ≈ 0.07 and p max ≈ 0.2 (carriers per site).…”
mentioning
confidence: 99%